Efficient synthesis of boronate affinity-based chlorogenic acid-imprinted magnetic nanomaterials for the selective recognition of chlorogenic acid in fruit juices. (19th June 2020) - Li, Guanfeng; Shi, Zehua; Li, Daojin
Abstract : Chlorogenic acid (CGA), a cis -diol-containing compound, can exhibit anti-inflammatory, antiviral, antimicrobial and anti-oxidation properties. Abstract : Chlorogenic acid (CGA), a cis -diol-containing compound, can exhibit anti-inflammatory, antiviral, antimicrobial and anti-oxidation properties. Thus, it is essential to determine CGA in food products. However, analysis of CGA at natural levels in food products is difficult because of its very low concentration level and the presence of undesirable matrix effects which could interfere with the measuring system. Thus, it is essential to develop efficient and selective enrichment approaches for determining CGA. Molecularly imprinted polymers can be well used for the selective enrichment of CGA from food samples. In this study, we utilized CGA-imprinted magnetic nanoparticles as an ideal sorbent for selective enrichment of CGA followed by direct absorbance determination. The CGA-imprinted magnetic nanoparticles were prepared according to a newly reported strategy, called boronate affinity-based oriented surface imprinting. Magnetic nanoparticles and boronic acid ligands were used as supporting materials and functional monomers, respectively. The prepared CGA-imprinted magnetic nanoparticles exhibited several significant advantages, such as good specificity, high binding affinity and low binding pH toward CGA, which made the molecularly imprinted material an ideal sorbent for selective enrichment of CGA. The prepared CGA-imprinted magnetic nanoparticles were successfully applied to the analysis of CGA in fruit juices.